Attentive Miron. Ecocritical motifs in the prose of Miron Białoszewski - Bulewicz, Ewelina (Hybris, 2022)
Ten years have just passed since the publication of Tajny dziennik and Miron Białoszewski’s prose continues to demand the discovery of new threads in it; also, in the context of the Anthropocene. The aim of my article will be to analyze and interpret the ecocritical motifs present in the works of the author of Pamiętnik z powstania warszawskiego, which oscillate around the relation between the author-narrator and non-human others. The subject of my research will be two important prose volumes written by Białoszewski in the mid-1970s: Konstancin and Chamowo, which have been relatively little studied in the context of posthumanism or the category of attentiveness. In this article I will present the attitude of the author to animals, plants, and garbage, which has been partially discussed by Agnieszka Karpowicz in her works. Moreover, I will prove that each of the aforementioned motifs perfectly fits into the current discourse on human-animal, nature-culture relations.